Issues of Tuberculosis Drug-Resistance in Kharkiv Region and in Ukraine - O.S. Shevchenko; O.O. Pohorielova (Civic Union "Communicable Diseases Intensive Care Association", 2019)
Background. Multidrug-resistant tuberculosis and extensively drug-resistant tuberculosis remain severe epidemic problems in the world. That's why the purpose of our study was to investigate the dynamics of the incidence of multidrug-resistant and extensively drug-resistant tuberculosis, the structure of cases and the effectiveness of treatment in this category of patients in the Kharkiv region and in Ukraine. Materials and methods. To perform the study, data from reporting forms No. 4-2 (TB 07 - MDR TB), No. 8-6 (TB 08) and data from analytical and statistical reference books "Tuberculosis in Ukraine" were used. Statistical processing of information was carried out using Statistica 7.0, Microsoft Office Excel 2007. Results. We found a relatively consistently high incidence rate, prevalence of tuberculosis recurrences among patients with drug-resistant tuberculosis, an increase in the proportion of extensively-drug resistance in patients with treatment failure and interrupted treatment, and low effectiveness of treatment of multidrug-resistant and extensively drug-resistant tuberculosis in patients with repeated cases of treatment. Conclusions. The obtained data once again emphasizes the need for the selection of adequate schemes for antituberculosis chemotherapy and control of anti-tuberculosis drugs.